Analysis on vaccine hesitation and its associated factors among parents of preschool children in Songgang Street, Shenzhen - Shen, Xin; Wu, Xia; Deng, Zhenyu; Liu, Xiang; Zhu, Yi; Huang, Yuchai; Deng, Yuhua; Tian, Qingfeng; Gan, Yong; Gong, Yanhong; Lu, Zuxun (Scientific reports, 2022)
China has the largest number of vaccinated population around the world. However, there has been few research on the prevalence and associated factors of vaccine hesitation among parents of preschool children. Therefore, we conducted this study to evaluate the status of vaccine hesitation and its associated factors among children’s parents. A cluster random sampling method was adopted to select six community health service centers in Shenzhen, and parents of preschool children who were immunized in the vaccination outpatient department of the selected community health centers were surveyed using a structured self-administered questionnaire. Vaccine hesitation was assessed by the Parent Attitudes about Childhood Vaccines (PACV) scale. A multiple linear regression analysis was used to assess the associated factors for vaccine hesitance among children's parents. A total of 1025 parents (response rate, 93.18%) filled out the questionnaires. The average score of vaccine hesitancy was 43.37 (SD = 10.34) points. 23.61% of parents wanted children to get all the recommended shots, 53.76% of them did not believe that many of the illnesses shots prevent were severe, and 75.41% of them could not guarantee the information they receive about shots. The results of multiple linear regression showed that the number of children in the family ( β = −0.93, 95% CI: −1.31 to 0.54), health status of the child ( β = 0.47, 95% CI: 0.07 to 0.87), education level of the parents (Father: β = −0.84, 95%CI: −1.37 to 0.31; Mother: = −1.59, 95%CI:−2.13 to −1.05), and annual family income ( β = 1.64, 95%CI: 1.13–2.16) were significantly associated with vaccine hesitation. The average score of parents' vaccine hesitation in Shenzhen was 43.37. The results showed that the number of children in the family, health status of the children, education level of the parents and annual family income were important factors associated with the parents' vaccine hesitation.